The fibrinolytic potential of Bacillus amyloliquefaciens isolates from salt-fermented shrimp paste terasi (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Pinontoan R, City S, Widjaja AN, Purnomo JS, Dikson. 2024. The fibrinolytic potential of Bacillus amyloliquefaciens isolates from salt-fermented shrimp paste terasi. Biodiversitas 25: 3193-3199. Thrombosis, a major pathology in Cardiovascular Diseases (CVDs), significantly contributes to global mortality. Although medicinal prevention and management of recurrent thromboses do exist, alternative means using natural sources are actively sought because of their lower costs, better compatibility, and lower risks of side effects. Due to their beneficial microorganisms, fermented foods offer a potential thrombolytic source for managing CVDs. In this study, we aimed to isolate and identify bacteria with thrombolytic activity from fermented shrimp paste terasi. Potential protease-producing bacteria from terasi were determined via cell and colony morphology, biochemical properties, and 16S rRNA sequence analyses. Subsequently, the thrombolytic and fibrinolytic activities of the bacteria were assessed by performing whole-blood clot tests and fibrin degradation assays; two protease-producing bacteria, designated as TJU5 and TMAD4 isolates were identified as Bacillus amyloliquefaciens. The isolates demonstrated thrombolytic activity by significantly reducing whole-blood clot mass after 2 h of incubation. The thrombolytic mechanism involves fibrinolysis indicated by the rapid degradation of A?, B?, and ? fibrin chains observed within 1 min of incubation. These findings highlight the beneficial bacteria from fermented shrimp paste terasi, identified as B. amyloliquefaciens TJU5 and TMAD4, with high thrombolytic and fibrinolytic activities, underscoring their potential role in bolstering cardiovascular health.
Keywords: Bacillus amyloliquefaciens, cardiovascular health, fibrinolytic, terasi, thrombolytic